Differentiating Branch Duct and Mixed IPMN in Endoscopically Collected Pancreatic Cyst Fluid via Cytokine Analysis - Linda S. Lee; Andrew M. Bellizzi; Peter A. Banks; Nisha I. Sainani; Vivek Kadiyala; Shadeah Suleiman; Darwin L. Conwell; Joao A. Paulo (Gastroenterology Research and Practice)
Background. Differentiating branch duct from mixed intraductal papillary mucinous neoplasm (BD-IPMN) is problematic, but clinically important as mixed IPMNs are managed surgically, while some BD-IPMN may be followed. Inflammatory mediator proteins (IMPs) have been implicated in acute and chronic inflammatory and malignant pancreatic diseases. Aim. To compare IMP profile of pancreatic cyst fluid collected endoscopically from BD-IPMN and mixed IPMN. Methods. Pancreatic cyst fluid from ten patients (5 BD-IPMN and 5 mixed IPMN) was collected by endoscopic ultrasound-guided fine needle aspiration or endoscopic retrograde cholangiopancreatography. Concentrations of 89 IMPs in these samples were determined using a multiplexed bead-based microarray protein assay and compared between BD-IPMN and mixed IPMN. Results. Eighty-six of 89 IMPs were detected in at least one of the 10 samples. Fourteen IMPs were detected only in mixed IPMN, while none were only in BD-IPMN. Of these, TGF-β1 was most prevalent, present in 3 of 5 mixed IPMNs. Seventy-two IMPs were detected in both BD-IPMN and mixed IPMNs. Of these, only G-CSF (P<0.05) was present in higher concentrations in mixed IPMNs. Conclusion. TGF-β1 and G-CSF detected in endoscopically collected pancreatic cyst fluid are potential diagnostic biomarkers capable of distinguishing mixed IPMN from BD-IPMN.